2015
DOI: 10.1176/appi.ajp.2015.14091185
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric-Onset and Adult-Onset Separation Anxiety Disorder Across Countries in the World Mental Health Survey

Abstract: Objective The age-at-onset criterion for separation anxiety disorder was removed in DSM-5, making it timely to examine the epidemiology of separation anxiety disorder as a disorder with onsets spanning the life course, using cross-country data. Method The sample included 38,993 adults in 18 countries in the World Health Organization (WHO) World Mental Health Surveys. The WHO Composite International Diagnostic Interview was used to assess a range of DSM-IV disorders that included an expanded definition of sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
73
2
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 30 publications
5
73
2
5
Order By: Relevance
“…Adult separation anxiety disorder (ASAD) has recently been reported in the psychiatric literature across the globe and diagnostic and statistical manual (DSM) of mental disorder omitted the age 18 years criterion for diagnosis of separation anxiety disorder (SAD) (1,2). Adult onset ASAD refers to separation anxiety disorder in an adult without a prior documented history of childhood separation anxiety disorder (3,4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult separation anxiety disorder (ASAD) has recently been reported in the psychiatric literature across the globe and diagnostic and statistical manual (DSM) of mental disorder omitted the age 18 years criterion for diagnosis of separation anxiety disorder (SAD) (1,2). Adult onset ASAD refers to separation anxiety disorder in an adult without a prior documented history of childhood separation anxiety disorder (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Adults with ASAD experience intense anxiety about separation from their attachment figures and engage themselves in wide ranges of activities to avoid separation and may show different emotional and behavioral disturbances that may lead to functional deterioration (1,5). Previous research revealed different factors responsible for developing ASAD, such as childhood experiences (2), environmental factors (6), genetic factors (7), over protective parenting (1,3), lack of healthy self (7), and collectivistic cultures (3). This recent recognized disorder affects multiple domains of life and is associated with different comorbidities that ultimately decrease quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…9,15 Insecure attachment styles and separation anxiety can increase risk of development of PTSD. [15][16][17] Reciprocally, PTSD itself can unmask/lead to insecure attachment relationships even in adulthood. 16,17 The authors note the huge public health burden of PTSD in veterans.…”
mentioning
confidence: 99%
“…[15][16][17] Reciprocally, PTSD itself can unmask/lead to insecure attachment relationships even in adulthood. 16,17 The authors note the huge public health burden of PTSD in veterans. It will benefit veterans and civilians with PTSD for us to intervene rapidly and to attempt to better pinpoint risk factors around which to structure earlier interventions.…”
mentioning
confidence: 99%
“…The study by Derrick Silove, M.D., Ph.D., et al (1), in this issue of the Journal , on pediatric- and adult-onset separation anxiety disorder across countries in the World Mental Health Survey, an epidemiologic report of separation anxiety disorder in a sample of 38,993 adults in 18 countries, is an eye-opening study that will contribute to a better appreciation of anxiety disorders across the lifespan. Methods in this extraordinary study are clearly articulated and exemplary.…”
mentioning
confidence: 99%